Experimental Design of a Filtration System in Electroplating Wastewater Treatment - Dita Yulianty Nur Sholehah Dwinda; Budiyan Mariyadi; Arief Yunan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2026)
Electroplating waste contains heavy metals and toxic compounds such as zinc (Zn) and cyanide (CN) that have the potential to pollute the environment, so effective treatment methods are needed before disposal. This study aims to design and test a filtration system on palm oil, zeolite, activated charcoal, and silica sand media as free variables and Zn, CN, and pH levels as fixed variables using a random complete block experimental design method. Media Arrangement Factor (A) consists of 4 levels, namely A1, A2, A3 and A4. And the media volume factor (B) consists of 2 levels, namely B1-B2. The combination of treatments that occur between the composition and volume of the media is A1B1, A1B2, A2B1, A2, B2, A3B1, A3B2, A4B1, A4B2. Then laboratory tests and ANOVA statistical tests were carried out to determine the effect of treatment. The results showed that the A4B2 treatment (composition of palm oil–zeolite–activated charcoal–silica sand with a volume of 1,140 grams) gave the best performance with a decrease in Zn by 86.5%, CN by 7.43%, and pH by 27.04%. The ANOVA test indicated that only the media composition factor had a significant influence on CN levels, while Zn and pH, the media composition and volume had a significant influence. Keywords: Electroplating wastewater, filtration, zinc (Zn), cyanide (CN), ANOVA